Adhesive Hydrogel Patch with Enhanced Strength and Adhesiveness to Skin for Transdermal Drug Delivery. (19th August 2020) - Jung, Hooyeon; Kim, Min Kyung; Lee, Jun Yup; Choi, Seung Woo; Kim, Jaeyun
Abstract: Transdermal drug delivery patches based on hydrogels are widely used for the transdermal delivery of diverse drugs. However, most hydrogels do not exhibit adequate adhesiveness to skin surface. Herein, tissue adhesive hydrogels consisting of polyacrylamide/polydopamine (PAM/PDA) hydrogels embedded with extra‐large pore mesoporous silica nanoparticles (XL‐MSNs) are proposed based on the synergy of cohesive and adhesive properties. The incorporation of XL‐MSNs leads to enhanced strength and adhesiveness to skin tissue due to an increased cohesive property derived from molecular interactions between XL‐MSNs and polymer chains. The application of XL‐MSNs to the hydrogel–skin tissue interface leads to a further enhanced adhesiveness due to the adhesive gluing role of XL‐MSNs on the interface. The optimized condition enables a 4.9‐fold increase in adhesion energy on the porcine skin tissue, compared to the control PAM/PDA patch. Strong adhesion is achieved immediately after the hydrogel patch is attached onto the skin as well as the surfaces of other organs. Finally, transdermal drug delivery through porcine skin is demonstrated by using the hydrogel patch, with a model drug loaded in the XL‐MSNs embedded in the patch. These observations indicate a simple but highly effective strategy for preparing a highly adhesive hydrogel patch for transdermal drug delivery. Abstract : The incorporation of extra‐large pore mesoporous silica nanoparticles in adhesive polyacrylamide/polydopamine hydrogels and the additional application of the mesoporous silica nanoparticles on the hydrogel–tissue interface lead to a significant enhancement of the strength and adhesiveness of the hydrogel. The rapid adhesion and sustained drug delivery through the skin allow a highly adhesive hydrogel patch for transdermal drug delivery.